A novel methodology to update the reliability of the corroding natural gas pipeline by introducing the effects of failure data and corrective maintenance. (January 2019) - Yu, Weichao; Zhang, Jie; Wen, Kai; Huang, Weihe; Min, Yuan; Li, Yichen; Yang, Xiaoyu; Gong, Jing
Abstract: By introducing the effects of the failure data and corrective maintenance, a novel methodology has been established to update the reliability of the corroding natural gas pipeline. Firstly, the methodology is able to calculate the failure probabilities for the small leak and burst based on the inspection data. The rank regression method is then applied to determine the fittest failure distribution function. Moreover, the failure distribution functions are updated by considering the failure data and the corrective maintenance. The Bayesian method and Markov Chain Monte Carlo (MCMC) simulation techniques are employed in the update process. Furthermore, the actual data from a natural gas pipeline located in China is used to illustrate this methodology, and the assessment indicates that the failure data and the corresponding corrective maintenance exert great impact on failure probability.